Design and optimization of an open personalized human-computer interaction system for New Year Painting based on the learner's model - Muhamad Firdaus Ramli (Tanjung Malim, 2024)
Design and optimization of an open personalized human-computer interaction system for New Year Painting based on the learner's model by Muhamad Firdaus Ramli